2019
DOI: 10.1007/s11738-019-2878-x
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminolevulinic acid (ALA) promotes primary root elongation through modulation of auxin transport in Arabidopsis

Abstract: The specific function of 5-aminolevulinic acid (ALA), a new plant growth regulator, in modulating root growth of plants and the mechanisms underlying ALA-regulated root growth are largely unknown. Here, Arabidopsis seedlings were photographed and collected before and after ALA or 2,3,5-triiodobenzoic acid (TIBA) treatment for determination of root growth, fluorescence intensities of PIN1, PIN2, PIN7, and DR5, and gene expression levels of auxin synthesis, signaling, and transport. We first demonstrated that AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 52 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…The application of ALA also improved the total and reducing sugars, fruit weight and volume, and flesh percentage in date palm [ 106 ]. This improvement in plant growth and productivity is generally associated with all pathways involved in root growth (particularly the mechanism of auxin transport and biosynthesis) [ 107 ], chlorophyll biosynthesis, and total chlorophyll content [ 33 ], which are associated with improved yield and fruit quality ( Table 3 , and Figure 4 and Figure 5 ) due to an increased photosynthetic rate [ 14 ]. It was reported that ALA inhibits ABA-induced stomatal closure via the reduction of the H 2 O 2 and Ca 2+ levels in guard cells and simultaneously improves the photosynthesis of stressed plants [ 108 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of ALA also improved the total and reducing sugars, fruit weight and volume, and flesh percentage in date palm [ 106 ]. This improvement in plant growth and productivity is generally associated with all pathways involved in root growth (particularly the mechanism of auxin transport and biosynthesis) [ 107 ], chlorophyll biosynthesis, and total chlorophyll content [ 33 ], which are associated with improved yield and fruit quality ( Table 3 , and Figure 4 and Figure 5 ) due to an increased photosynthetic rate [ 14 ]. It was reported that ALA inhibits ABA-induced stomatal closure via the reduction of the H 2 O 2 and Ca 2+ levels in guard cells and simultaneously improves the photosynthesis of stressed plants [ 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both PIN1 and PIN7 mainly regulate acropetal auxin transport, while PIN2 specifically influences the basipetal auxin transport [ 111 , 112 ]. An et al [ 107 ] reported that ALA regulates PIN proteins at both the transcriptional and post-transcriptional levels and its effect on root growth in a concentration-dependent manner. Low concentrations (e.g., 10 mg·L −1 ) improved root elongation, while higher concentrations (e.g., 20 mg·L −1 ) inhibited it but stimulated the initiation of lateral roots.…”
Section: Discussionmentioning
confidence: 99%
“…RCN1, one of the three PP2A scaffolding subunits in Arabidopsis (Deruere et al ), positively functioned in MeJA‐as well as ABA‐induced stomatal closure (Kwak et al , Saito et al ), further demonstrating a role of PP2A in guard cell signaling. ALA showed a broad crosstalk with other plant growth regulator, including ABA (An et al ), BR (Zheng et al ), auxin (An et al ) and ethylene (An YY, Hu S and Wang LJ unpublished data). In light of these reports, we speculate that PP2A may also participate in ALA signaling, including ALA‐regulated stomatal movement.…”
Section: Introductionmentioning
confidence: 99%
“…ALA is a growth regulator that regulates the growth and development of plants at different growth stages. Soaking seeds with ALA reduces the germination time and increases the germination index of pigeon pea, and promotes Arabidopsis thaliana root elongation by regulating auxin transport [ 8 , 72 ]. ALA significantly increased yields through root or foliar fertilization in grapevines ( Vitis vinifera ) [ 73 ].…”
Section: Application Of Ala In Agriculture and Medicinementioning
confidence: 99%